1996
DOI: 10.1099/13500872-142-7-1895
|View full text |Cite
|
Sign up to set email alerts
|

Intra-specific diversity and host specificity within Pasteurella haemolytica based on variation of capsular polysaccharide, lipopolysaccharide and outer-membrane proteins

Abstract: Intra-specific diversity within Pasteurella haemolytica was assessed by analysing variation in the capsular polysaccharide (serotypes), lipopolysaccharide (LPS) and outer-membrane proteins (OMPs) of 184 isolates recovered from cattle and sheep. Four of 12 serotypes comprised 83% of the total number of isolates, including A1 and A2 as the most frequently recovered serotypes from cattle and sheep, respectively. Nine distinct LPS profiles were identified. Four different core-ol igosaccharide patterns were present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 7 publications
2
66
0
2
Order By: Relevance
“…Outer membranes were prepared by Sarkosyl extraction as described previously (Davies et al, 1992;Davies & Donachie, 1996). The protein concentrations were determined by the modified Lowry procedure (Markwell et al, 1978) and the OMPs were adjusted to 2·0 mg ml À1 in 20 mM Tris/HCl (pH 7·2) and stored at À85 8C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outer membranes were prepared by Sarkosyl extraction as described previously (Davies et al, 1992;Davies & Donachie, 1996). The protein concentrations were determined by the modified Lowry procedure (Markwell et al, 1978) and the OMPs were adjusted to 2·0 mg ml À1 in 20 mM Tris/HCl (pH 7·2) and stored at À85 8C.…”
Section: Methodsmentioning
confidence: 99%
“…The OMPs were separated by SDS-PAGE in 12 % (w/v) resolving gels (Hoefer SE600 electrophoresis apparatus) using the SDS discontinuous system of Laemmli (1970) as described previously (Davies et al, 1992;Davies & Donachie, 1996). Unless otherwise stated, all samples were heated at 100 8C for 5 min prior to electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…For example, serotype A1 and A6 strains account for almost all cases of bovine pneumonic pasteurellosis, whereas serotype A2 and A7 isolates are the major causes of disease in sheep. It has also been shown that bovine and ovine isolates of the same serotype, e.g., A1, A2, or A6, can be distinguished by differences in chromosomal genotype (13) or outer membrane protein (OMP) profiles (10). The inference is that natural populations of M. haemolytica consist of distinct evolutionary lineages that are differentially adapted to either cattle or sheep (13).…”
mentioning
confidence: 99%
“…Serotypes A5 and A6 were recovered at very low rates (2.9% and 4.3% respectively) and serotypes A8, Al4 and A16 were not found at all. Interestingly enough, serotype A2 was the only one recovered from goats, suggesting that a much wider range of serotypes is ) and in ovine isolates from the UK, Germany and the USA (Davics and Donachic 1996). However the isolation rate of the remaining serotypes clearly varies among European countries.…”
Section: Discussionmentioning
confidence: 99%